Soluble Epoxide Hydrolase and Brain Cholesterol Metabolism - Domingues, Michelle Flores; Callai-Silva, Natalia; Piovesan, Angela Regina; Carlini, Celia Regina (Frontiers in Molecular Neuroscience, 2020)
The bifunctional enzyme soluble epoxide hydrolase (sEH) is found in all regions of the brain. It has two different catalytic activities each assigned to one of its terminal domains: the C-terminal domain presents hydrolase activity whereas the N-terminal domain exhibits phosphatase activity. The enzyme’s C-terminal domain has been linked to cardiovascular protective and anti-inflammatory effects. Cholesterol-related disorders have been associated with sEH, which plays an important role in the metabolism of cholesterol precursors. The role of sEH’s phosphatase activity has been so far poorly investigated in the context of the central nervous system physiology. Given that brain cholesterol disturbances play a role in the onset of Alzheimer’s disease as well as of other neurodegenerative diseases, understanding the functions of this enzyme could provide pivotal information on the pathophysiology of these conditions. Moreover, the sEH phosphatase domain could represent an underexplored target for drug design and therapeutic strategies to improve symptoms related to neurodegenerative diseases. This review discusses the function of sEH in mammals, its protein structure and catalytic activities. Particular attention was given to the distribution and expression of sEH in the human brain, deepening into the enzyme's phosphatase activity and its participation in brain cholesterol synthesis. Finally, this review focused on the metabolism of cholesterol and its association with Alzheimer's disease.